An intercomparison of statistical downscaling methods used for water resource assessments in the United States. Issue 9 (9th September 2014) - Gutmann, Ethan; Pruitt, Tom; Clark, Martyn P.; Brekke, Levi; Arnold, Jeffrey R.; Raff, David A.; Rasmussen, Roy M.
Abstract Information relevant for most hydrologic applications cannot be obtained directly from the native‐scale outputs of climate models. As a result the climate model output must be downscaled, often using statistical methods. The plethora of statistical downscaling methods requires end‐users to make a selection. This work is intended to provide end‐users with aid in making an informed selection. We assess four commonly used statistical downscaling methods: daily and monthly disaggregated‐to‐daily Bias Corrected Spatial Disaggregation (BCSDd, BCSDm), Asynchronous Regression (AR), and Bias Corrected Constructed Analog (BCCA) as applied to a continental‐scale domain and a regional domain (BCCAr). These methods are applied to the NCEP/NCAR Reanalysis, as a surrogate for a climate model, to downscale precipitation to a 12 km gridded observation data set. Skill is evaluated by comparing precipitation at daily, monthly, and annual temporal resolutions at individual grid cells and at aggregated scales. BCSDd and the BCCA methods overestimate wet day fraction, and underestimate extreme events. The AR method reproduces extreme events and wet day fraction well at the grid‐cell scale, but over (under) estimates extreme events (wet day fraction) at aggregated scales. BCSDm reproduces extreme events and wet day fractions well at all space and time scales, but is limited to rescaling current weather patterns. In addition, we analyze the choice of calibration data set by looking at both a 12 km and a 6 km observational data set; the 6 km observed data set has more wet days and smaller extreme events than the 12 km product, the opposite of expected scaling.